Mechanical Properties and Torque/Force Generation of XP-Endo Shaper, Trunatomy, Spring Endo File, and Spring Endo Heated Finish File, Part 1 - Soram Oh; Bong-Ki Jeon; Seok Woo Chang (Applied Sciences, 2022)
We evaluated the mechanical properties and torque/force generated during canal shaping by four NiTi files with innovative designs. Each of the 52 TruNatomy Prime, XP-endo Shaper, Spring Endo files with unheated finish (Spring Endo), and Spring Endo files with heated finish (Spring H) were subjected to bending, buckling, cyclic fatigue, and torsional resistance tests (n = 10 per NiTi file type). Canal shaping was simulated with J-shaped resin blocks (n = 10). Phase transformation behavior was investigated using differential scanning calorimetry (n = 2). Statistical analysis was performed by one-way ANOVA and the Games-Howell test. Spring Endo and Spring H files showed higher bending and buckling resistances, ultimate torsional strength, and elastic modulus than TruNatomy and XP-endo Shaper (p < 0.05). XP-endo Shaper demonstrated the highest cyclic fatigue resistance and angle of rotation to fracture (p < 0.05). The elastic modulus increased in the order of XP-endo Shaper, TruNatomy Prime, Spring H, and Spring Endo. During simulated canal shaping, XP-endo Shaper generated greater clockwise torque and less screw-in force compared to Spring Endo files, with superior cutting ability. TruNatomy Prime generated the least clockwise torque and screw-in force. At room temperature, TruNatomy and XP-endo Shaper files consisted of mixed phases of austenite, martensite, and R-phase; Spring H files consisted of martensite; and Spring Endo files consisted of austenite.